Retinal detachment and herpesvirus retinitis in patients with AIDS. Issue 6 (June 1995) - Dowler, J G; Towler, H M; Mitchell, S M; Cooling, R J; Lightman, S L
Abstract : BACKGROUND--The prolongation of survival of patients with herpesvirus retinitis and AIDS has been associated with a rise in the incidence of retinal detachment. In such cases, however, retinal reattachment may be difficult to achieve, and postoperative visual acuity may be poor despite anatomically successful surgery. METHODS--In order to examine factors affecting the visual outcome of surgery, a retrospective review of 29 patients with retinal detachment, herpesvirus retinitis, and AIDS was performed. Retinal reattachment surgery (32 procedures) or prophylactic laser demarcation (five procedures) was performed in 28 eyes of 23 patients. RESULTS--The macula was attached in 23/28 (82%) eyes at the last outpatient visit. Best postoperative visual acuity (median 6/18, range 6/6-hand movements) was significantly greater than final postoperative acuity (median counting fingers, range 6/6-no perception of light) (Wilcoxon sign rank test, p = 0.003), and was retained for a median of 3 months (1-91 weeks) after surgery. Poor visual outcome as evidenced by submedian final visual acuity was invariably associated with persistence of macular detachment, and significantly associated with the occurrence of optic atrophy (odds ratio = 5, p = 0.02). CONCLUSION--Retinal reattachment surgery appears justified in patients with herpesvirus retinitis and AIDS, but postoperative visual deterioration may occur in association with optic atrophy.